PENGARUH WAKTU PERENDAMAN Ca(OH)2 DAN KONSENTRASI GULA TERHADAP KARAKTERISTIK JELLY CANDY BUAH PALA - Adinda, Sekar; Fahrizal, Fahrizal; Hasni, Dian (Politeknik ATI Padang, 2024)
This research aims to see the effect of soaking nutmeg in a solution of whiting (Ca(OH)2) and the added sugar concentration on the characteristics of the jelly candy produced. This study used a factorial randomized block design (RAK) with 2 factors, namely the duration of soaking nutmeg flesh with lime solution (L) and sugar concentration (K). Factor 1, namely the duration of soaking with lime solution (L), consists of 3 levels, namely L1 (12 hours), L2 (24 hours), and L3 (36 hours). Factor 2, namely sugar concentration (K), consists of 3 levels, namely K1 60%, K2 80%, and K3 100% of the weight of nutmeg flesh. The results of the study showed that the duration of soaking in lime solution had a very significant effect on the water content, pH, reducing sugar, and astringent taste of the resulting nutmeg jelly candy. Sugar concentration has a very significant effect on reducing the soft texture of nutmeg jelly candy produced. The interaction of soaking time in lime solution and sugar concentration has a very significant effect on water content, reducing sugar, astringent taste, sweet taste, and soft texture of nutmeg jelly candy produced. Based on organoleptic value, the best treatment based on the ranking method, nutmeg fruit flesh soaked in lime solution for 12 hours and 100% sugar concentration (L1K3), is the best combination of treatments in making nutmeg jelly candy, which produces jelly candy with a water content of 21.90%, an ash content of 1.66%, pH 5.17, reducing sugar to 20.49%, and an and an organoleptic color (opaque appearance). 3.68 (neutral), shiny appearance 3.67 (neutral) aroma 3.67 (neutral), sweet taste 4.48 (neutral) astringent taste 4.68 (rather strong) soft texture 2.57 (rather weak) and chewy texture 3.58 (neutral).